MANAJEMEN RISIKO KEUANGAN: STUDI KASUS PADA PERUSAHAAN STARTUP DI INDONESIA - Resa Rosita; Rika Sahara; Amanda Putri Asmara; Sunita Dasman (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2025)
This study aims to analyze financial risk management in technology startup companies in Indonesia, with a case study of PT GoTo Gojek Tokopedia Tbk. Through a quantitative descriptive approach, this study uses secondary data from the company's financial statements for the period 2020-2022. The results showed that although PT GoTo was able to maintain liquidity above industry standards, the company faced challenges in financial management due to the downward trend in several financial ratios. The merger decision between Gojek and Tokopedia has a positive impact on sales growth, which reached a significant increase of 150.2% in 2022. The implications of this study indicate that tech startups need to implement a comprehensive financial management strategy, focusing on liquidity management, optimal capital structure, and funding diversification to effectively manage financial risks.